The value of family visits as an implementation of maintaining human dignity: a sociological perspective - Teresia Noiman Derung (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Family visits are urgently needed at this time because violence in the family is rife and has even increased from time to time. Victims of violence are generally women and children. The cause of violence in the family is due to a shift in understanding regarding the image of God that exists in humans to become a "means" that can be used to satisfy personal interests. Human dignity that belongs to God can be taken away by anyone and in any way. The purpose of writing this article is to describe the urgency of family visits as an implementation of maintaining human dignity in social life. The approach used is a descriptive qualitative approach with literature review methods from various sources, namely journals, Scriptures, books, and Church teachings. This paper uses text analysis according to the context experienced in a sociological perspective. The results found, family visits have three values that can be implemented to maintain human dignity, namely: first, building brotherhood as social beings in society. Second, listen to each other; and third protect each other against evil. Family visits are very important and needed by society at this time, because families need to be greeted, listened to, and protect each other from crime. This effort is made so that human dignity is maintained as the image of God. Advice for Christian families; carrying out family visits at this time is very important as an implementation of maintaining human dignity which has begun to shift due to scientific and technological developments in society.